Influence Of Counselling On Learning Difficulties In Post-Basic School History Curriculum In Katsina Zonal Education Quality Assurance - Muhammad, Yusuf Danladi (Anterior Jurnal, 2021)
Nigeria had accomplished its aged - long goal of revitalizing as well as restoring the teaching – learning of historical studies in the realm of schools system, purposely to utilize the tenets implicit in its curriculum design to stimulate universal prospective citizenship characteristics amongst generation of youths. However, the lingering existence of some difficulties in learning history among the senior secondary students seems to doom the aforementioned Nigeria’s hope to failure. This study therefore, surveyed the influence of counselling services rendered by school counselling masters on students to overcome learning difficulties of Post-Basic schools 2010 history curriculum. The research hypothesizes that: i. there is no significant influence of counseling service on resolving students’ difficulties in learning 2010 Post-Basic history curriculum. ii. there is no significant influence of counseling service on resolving teachers’ instructional challenges in implementing 2010 Post-Basic curriculum. Some 380 students offering history, 30 history teachers and 4 Post-Basic schools in Katsina Zonal Education Quality Assurance were randomly sampled for the study. The findings revealed insignificant influence of counselling service in resolving students’ learning difficulties and in resolving the teachers’ challenges in implementing the 2010 Post-Basic history curriculum.